(untitled) - Frendo, Evan (Oxford (New York), 2007)
This book has been specifically developed for people working in accounting and finance who need English to communicate in a variety of situations with colleagues and business partners. In this short course, you will learn the language related to accounting as well as ways to achieve your goals in meetings, in presentations, on the telephone, or when making small talk.
Keywords: English language,English language,English language,Accounting,Anh ngữ thương mại,Tiếng Anh thực hành; Study and teaching,Business English,English language